If tan A , tan B are roots of x 2 − P x + Q = 0 the value of sin 2 ( A + B ) is?
Note: P , Q are real numbers.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Here tan (a) +tan (b)=p and tan (a)×tan( b)=q . Substituting tan (a) by sin (a)/cos (a) and tan (b )by sin (b)/cos (b) in tan (a)+tan (b)=p, we get: sin (a) cos (b)+ cos (a) sin (b)= p×cos (a)×cos (b). Squaring both sides and replacing cos (a) by 1/sec (a) and cos (b) by 1/sec (b) we get: sin^2 (a+b) =p^2/(sec^2 (a)×sec^2 (b)). Now sec^2 (a)×sec^2 (b) = (1+tan^2 (a))(1+tan^2 (b))= 1+tan^2 (a)+tan^2 (b)+tan^2 (a)×tan^2 (b). Now: tan^2 (a)+tan^2 (b) =(tan (a)+tan (b))^2 - 2×tan (a)×tan (b)=p^2-2q and tan^2 a×tan^2 b=q^2. Therefore, sin^2 (a+b)=p^2/(1+p^2-2q+q^2) = p^2/(p^2+(1-q)^2).
Start with vieta's tan a + tan b = p , tan a tan b = q use an identity tan ( a + b ) = 1 − tan a tan b tan a + tan b now, substitute from vieta's tan ( a + b ) = 1 − q p ⟶ a + b = tan − 1 ( 1 − q p ) now, get both sides in sin 2 sin 2 ( a + b ) = sin 2 ( tan − 1 ( 1 − q p ) use the identity sin 2 θ = 2 1 ( 1 − cos 2 θ ) and we get sin 2 ( tan − 1 ( 1 − q p ) ) = 2 1 ( 1 − cos ( 2 tan − 1 ( 1 − q p ) ) use the identity cos ( 2 tan − 1 θ ) = θ 2 + 1 1 − θ 2 2 1 ( 1 − cos ( 2 tan − 1 ( 1 − q p ) ) = 2 1 ( 1 − ( 1 + ( 1 − q p ) 2 1 − ( 1 − q p ) 2 ) upon some expansion, sin 2 ( a + b ) = p 2 + ( 1 − q ) 2 p 2
It is not reduced the generalization, can assume that P=3 and Q=2. So this equation has two roots: x 1 = 1 , x 2 = 2 Applying to this problem, it has: t a n ( A ) = 2 , t a n ( B ) = 1 ⇒ s i n ( A ) = 2 c o s ( A ) , s i n ( B ) = c o s ( B ) c o s ( A ) = 5 1 , s i n ( A ) = 5 2 c o s ( B ) = s i n ( A ) = 2 1 s i n ( A ) c o s ( B ) + s i n ( B ) c o s ( A ) = 1 0 3 ⇒ s i n 2 ( A + B ) = P 2 + ( 1 − Q ) 2 P 2
Tan(A+B) = Tan A + tan B /{1-tan A tanB}
But tanA +tanB = P ........TanA tanB = Q Frm here we get tan A+B Acc.to Mr , phythagoras
sinA+B get opt a
Incomplete solution?
Problem Loading...
Note Loading...
Set Loading...
From the question, we get P = t a n A + t a n B and Q = t a n A t a n B .
Hence, t a n ( A + B ) = 1 − t a n A t a n B t a n A + t a n B = 1 − Q P .
By Pythagorean identity, s i n 2 θ + c o s 2 θ = 1 .
Also, c o s 2 θ s i n 2 θ = t a n 2 θ .
Combining the two equations, we get s i n 2 θ = t a n 2 θ + 1 t a n 2 θ .
Therefore, s i n 2 ( A + B ) = t a n 2 ( A + B ) + 1 t a n 2 ( A + B ) = ( 1 − Q P ) 2 + 1 ( 1 − Q P ) 2 = P 2 + ( 1 − Q ) 2 P 2 .